Rhizobacteria for the control of Meloidogyne in Capsicum annum L. in the greenhouse - Calvo-Araya, José Alonso; Valverde-Juárez, Victoria; Orozco-Aceves, Martha; Orozco-Muñoz, Arlette (Revista Mexicana de Ciencias Agrícolas, 2024)
The following study aimed to evaluate the effect of three plant growth-promoting bacteria: Bacillus amyloliquefaciens, Pseudomonas fluorescens and Streptomyces griseoviridis, and two types of fertilization: chemical and organic (vermicompost) in the soil for the control of root-knot nematode (Meloidogyne sp.), and their effect on the development of chili crops in the greenhouse. Four fertilizations, both chemical and organic, were carried out at the time of transplant and at 15, 30, and 45 days after transplant. The trial lasted five months. A total of nine treatments were established (three types of bacteria + one chemical control × two types of fertilization + one control with water), each of them with four replications, for a total of 36 plants. Measurements of galling percentage (GP) and galling index (GI) were made, and the efficiency of the treatments was determined. The dry and fresh weights of both the aerial part and the root of the plants were also determined. The highest degree of damage occurred in the control treatment with 71.2% GP, while the lowest GP was observed in the chemical fertilization × B. amyloliquefaciens treatment. The GI did not present significant differences between treatments because the negative effect of galling was counteracted by adequate root growth, which was especially visible in treatments such as chemical fertilization × B. amyloliquefaciens and organic fertilization × oxamyl.
Keywords: biological control; nematode; organic fertilization